2018
DOI: 10.3856/vol46-issue1-fulltext-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the contribution of dietary protein from poultry by product meal and fish meal to the growth of catfish Ictalurus punctatus by means of nitrogen stable isotopes

Abstract: ABSTRACT. The natural nitrogen stable isotope signatures (δ 15 N) found in poultry by-product meal (PBM) and fish meal (FM) were used to estimate the relative contribution of dietary nitrogen supplied by both ingredients to the somatic growth of juvenile channel catfish Ictalurus punctatus. Six isonitrogenous and isoenergetic experimental diets were formulated using FM and PBM. Two of these diets consisted of isotopic controls having only one ingredient supplying dietary nitrogen, either FM or PBM. Four combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several other studies also demonstrated that pet food grade poultry by-product meal could replace 650, 667 and 1,000 g/kg FM in the diets of catfish, Ictalurus punctatus, pompano, Trachinotus carolinus and fry grass carp, Ctenopharyngodon idella when 473, 150 and 300 g/kg FM were included in the control diets, respectively (García-Pérez et al, 2018;Rossi & Davis, 2012;Tabinda & Butt, 2012). In contrast, Nandakumar et al (2013) reported that dietary replacement of more than 100 g/kg FM with processed chicken waste meal as lipid oxidation, amino acid availability and reduced digestibility, which lead to poor growth performance when included at higher amount in fish diet (Nandakumar et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several other studies also demonstrated that pet food grade poultry by-product meal could replace 650, 667 and 1,000 g/kg FM in the diets of catfish, Ictalurus punctatus, pompano, Trachinotus carolinus and fry grass carp, Ctenopharyngodon idella when 473, 150 and 300 g/kg FM were included in the control diets, respectively (García-Pérez et al, 2018;Rossi & Davis, 2012;Tabinda & Butt, 2012). In contrast, Nandakumar et al (2013) reported that dietary replacement of more than 100 g/kg FM with processed chicken waste meal as lipid oxidation, amino acid availability and reduced digestibility, which lead to poor growth performance when included at higher amount in fish diet (Nandakumar et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…As FM has been substituted with poultry by-product meals, its suitability has been evaluated in many fish species, such as mirror carp, Cyprinus carpio (Emre et al, 2003), rainbow trout, Oncorhynchus mykiss (Steffens, 1994), cobia, Rachycentron canadum (Saadiah et al, 2011), sunshine bass (Morone chrysops × M. saxatilis) (Thompson et al, 2007), Florida pompano, Trachinotus carolinus (Rossi & Davis, 2012), Japanese seabass, Lateolabrax japonicas (Hu et al, 2013) and catfish, Ictalurus punctatus (García-Pérez et al, 2018). Wei et al (2006) also showed that up to 800 g/kg FM in diet of olive flounder could be replaced with poultry by-product meal (pet food grade) in considering the growth and apparent digestibility.…”
mentioning
confidence: 99%
“…Results from other trials on PM in diets for African catfish are mostly in line with the results of the present study. Authors testing up to 100% FM replacement with PM at an absolute level of PM inclusion of 6-47% (versus 56.4% in this study) generally recorded growth reduction and feed conversion impairment at the highest replacement levels in comparison to their control diets [75][76][77][78][79][80][81][82] and recommend FM replacement levels of 65% (30.6% PM inclusion) [82], 56% [80], 40% (17% PM inclusion) [78] and 30% (6.3% PM inclusion) [79]. However, [77] did not find significant differences in growth performance and feed conversion at 75-100% FM replacement (26-34.5% PM inclusion) compared to the FM control diet.…”
Section: Fish Performancementioning
confidence: 99%